Validation of the Indonesian version of Western Ontario and McMaster Universities osteoarthritis index in pre-elderly and elderly with osteoarthritis - Pande Made Yosira Hartana; Ni Luh Putu Gita Karunia Saraswati; Anak Agung Gede Eka Septian Utama; I Dewa Gede Alit Kamayoga (Universitas Udayana dan Diaspora Taipei Medical University, 2024)
Background: This study aimed to examine the psychometric performance of the Western Ontario and McMaster Universities osteoarthritis index (WOMAC) version Indonesia used in pre-elderly and older adults in Indonesia with knee osteoarthritis and hip osteoarthritis. Methods: This study obtained samples from 124 pre-elderly and elderly individuals affected by knee and hip osteoarthritis in the Denpasar, Badung, and Gianyar areas to check the reliability and validity of the Indonesia WOMAC from Karsten et al. (2019). Knee and hip osteoarthritis were examined using the American College of Rheumatology (ACR) clinical criteria. Results: The Indonesian WOMAC was valid with a score of (0.809-0.964) for knee osteoarthritis, (0.870-0.982) for hip osteoarthritis, and (0.744-0.944) for knee osteoarthritis and hip osteoarthritis. It is reliable with Cronbach’s alpha score of (α = 0.992) for knee osteoarthritis, (α = 0.996) for hip osteoarthritis, and (α = 0.980) for knee osteoarthritis and hip osteoarthritis in pre-elderly and elderly patients. Conclusion: Based on the research results, the Indonesian WOMAC was valid and reliable for knee and hip osteoarthritis and is used in pre-elderly and elderly patients.